Effect of an Immersive Preoperative Virtual Reality Experience on Patient Reported Outcomes: A Randomized Controlled Trial. Issue 6 (June 2017) - Bekelis, Kimon; Calnan, Daniel; Simmons, Nathan; MacKenzie, Todd A.; Kakoulides, George
Abstract : Objective: To investigate the effect of exposure to a virtual reality (VR) environment preoperatively on patient-reported outcomes for surgical operations. Background: There is a scarcity of well-developed quality improvement initiatives targeting patient satisfaction. Methods: We performed a randomized controlled trial of patients undergoing cranial and spinal operations in a tertiary referral center. Patients underwent a 1:1 randomization to an immersive preoperative VR experience or standard preoperative experience stratified on type of operation. The primary outcome measures were the Evaluation du Vecu de l'Anesthesie Generale (EVAN-G) score and the Amsterdam Preoperative Anxiety and Information (APAIS) score, as markers of the patient's experience during the surgical encounter. Results: During the study period, a total of 127 patients (mean age 55.3 years, 41.9% females) underwent randomization. The average EVAN-G score was 84.3 (standard deviation, SD, 6.4) after VR, and 64.3 (SD, 11.7) after standard preoperative experience (difference, 20.0; 95% confidence interval, CI, 16.6–23.3). Exposure to an immersive VR experience also led to higher APAIS score (difference, 29.9; 95% CI, 24.5–35.2). In addition, VR led to lower preoperative VAS stress score (difference, −41.7; 95% CI, −33.1 to −50.2), and higher preoperative VAS preparedness (difference, 32.4; 95% CI, 24.9–39.8), and VAS satisfaction (difference, 33.2; 95% CI, 25.4–41.0) scores. No association was identified with VAS stress score (difference, −1.6; 95% CI, −13.4 to 10.2). Conclusions: In a randomized controlled trial, we demonstrated that patients exposed to preoperative VR had increased satisfaction during the surgical encounter. Harnessing the power of this technology, hospitals can create an immersive environment that minimizes stress, and enhances the perioperative experience. Abstract : Supplemental Digital Content is available in the text